THE EFFECT SPRAYING NUTRITION SOLUTION ON TOTAL YIELD OF TWO CUCUMBER HYBRID ( Cucmis sativus L. ) - Abdulrahman , Harith B.; zedan, Ghassan J.; Aied, Kuteba Y. (Diyala Agricultural Sciences Journal, 2013)
The field experiment was conducted in plastic house of Horticulture and landscape design department at the season 2012 to study the effect of five foliar nutrition treatments ( Control , Giant , Protec , Viviter , and Lelli 2000 ) with two kind of hybrids ( Summit , Maxeem ) . Split plot design was used an distributed as R.C.B.D. . It was done with three replicates . The results showed that Viviter had superior significant in total chlorophyll content , Fruit weight , Plant yield , Total soluble soled so it gave higher rate reached 39.850 , 87.604 gm , 2148.87 gm , and 3.428% successively . Giant had superiority in fruit length , while Protec had superiority in fruit diameter , fruit numbers . While the control gave increasing in fruit hardness . Maxeem showed significant superiority in fruit length and fruit numbers while Summit had significant increasing in fruit diameter , fruit weight . The interaction between Viviter and Maxeem significant increasing in leaf chlorophyll content , fruit length , T.S.S. , while the interaction Lelli 2000 with summit had superiority in fruit diameter only . The interaction between Giant and Maxeem had significant superiority in fruit number while the interaction between Viviter and Summit had significant superiority in fruit weight . The significant superiority of plant yield was the interaction between Protec and Maxeem so it gave higher rate reached 2254.01 gm while the Control of Maxeem showed superiority in fruit hardiness